Ecological Implications of Soil Seed Bank in Conservation of Grassland of Moist Tropics, India: Exploring the Role of Soil Seed Bank in Conservation of Moist Tropical Grassland (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Backgrounds: Grassland is one of the most important ecosystems of the world which benefits human directly or indirectly needs to be conserved. Aims: To examine whether and to what extent soil seed bank has significant role in conservation of grassland of moist tropics.Methods: Seedling emergence method (seeds m-2) was used for analysis of soil seed bank. Phyto-sociological studies (IVI, biodiversity parameters, similarity index,) were carried out for both soil seed bank and above-ground vegetation. ANOVA, PCA, correlation, regression were used for different statistical analyses. Results: Large quanta of viable seeds (28450-30750 seeds m-2) were germinated in moist tropical grassland. Significant seasonal (p < 0.001) and depth variation were found in germination of seed from soil seed bank. Mainly persistent seed banks play important role in conservation. Most of the species were common in both soil seed bank and above-ground vegetation. High similarity (0.72, 0.55) and positive moderate correlation (r2 = 0.25, p < 0.05) was found between seed bank and above-ground vegetation. Conclusion: This result predicted that seed bank can be one of the best options for in situ conservation of grassland of moist tropics, as many others were also reported for various ecosystems of the world.Key-Words: Soil Seed Bank; Above-Ground Vegetation; Biodiversity Indices; Principal Component Analysis; Grassland Ecosystem; Moist Tropics.